2020
DOI: 10.1371/journal.pone.0243007
|View full text |Cite
|
Sign up to set email alerts
|

Silicon supplementation affects mineral metabolism but not bone density or strength in male broilers

Abstract: Because leg injuries produce welfare concerns and impact production for broilers, numerous interventions have been suggested as potential solutions. One mineral which may affect bone quality is silicon. The objective of this study was to determine if supplementing bioavailable silicon could affect bone morphology, mineralization, and strength without negatively influencing welfare and meat quality. Male broilers were raised from d 1 after hatching until 42 d of age and randomly assigned to treatment groups for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 59 publications
0
2
0
1
Order By: Relevance
“…Sums of standardized Si intakes in studies demonstrating positive effects on bone and/or mineral metabolism did rank higher in the Mann-Whitney U test than standardized Si intakes in studies showing no effects on bone or mineral metabolism. The difference between these two groups indicates that there may be a level above essentiality at which supplemented Si positively influences these outcomes, though some studies have reported no greater outcomes with increased supplementation [15,26,40,43,45,55]. Previous experiments that have achieved improvements in bone or cartilage quality in adult animals [5,15,27,48,49,[53][54][55] fed Si in large amounts, which, when expressed on a per kg BW basis at 18 to 462 mg Si/kg BW, is difficult to translate into use with large animals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sums of standardized Si intakes in studies demonstrating positive effects on bone and/or mineral metabolism did rank higher in the Mann-Whitney U test than standardized Si intakes in studies showing no effects on bone or mineral metabolism. The difference between these two groups indicates that there may be a level above essentiality at which supplemented Si positively influences these outcomes, though some studies have reported no greater outcomes with increased supplementation [15,26,40,43,45,55]. Previous experiments that have achieved improvements in bone or cartilage quality in adult animals [5,15,27,48,49,[53][54][55] fed Si in large amounts, which, when expressed on a per kg BW basis at 18 to 462 mg Si/kg BW, is difficult to translate into use with large animals.…”
Section: Discussionmentioning
confidence: 99%
“…If a human weighing 65 kg consumed the mean standardized Si intake from Si treatments, this would be 7.8 g Si, eclipsing the recommendation from the literature for this mineral as well as the daily recommended allowance for macrominerals like calcium [62]. Supplementing at these amounts would likely alter the metabolism of other crucial minerals [24,27,43,55] and would likely be difficult, if not impossible, to achieve in humans.…”
Section: Discussionmentioning
confidence: 99%
“…The blood serum analysis showed significant differences in ALP concentrations between male and female chickens due to various causal factors (Table 2). Proper nutrition, growing rate, and mechanical loading greatly influence bone quality development [41]. Male chickens tend to grow faster and heavier than females, which can lead to femoral degeneration in young birds [42].…”
Section: Alkaline Phosphatase Activitymentioning
confidence: 99%
“…Для фермерских хозяйств определяющим экономическим фактором служит качество яичной скорлупы. При средней производительности небольшой птицефабрики 300 млн яиц в год около 24 млн яиц выводятся из коммерческого оборота из-за мягкой скорлупы или ее разлома (6)(7)(8).…”
unclassified